KEBERADAAN CORPORATE GOVERNANCE DAN KONDISI FINANCIAL DISTRESSED TERHADAP VOLUNTARY DISCLOSURE - Riesanti Edie Wijaya (Jurnal Keuangan dan Perbankan, 2009)
Voluntary disclosure meant giving information to public either about fi nancial or non-fi -nancial regarding the fi rms operations without any legal requirement (Fishman and Hagerty, 1997).Giving information about voluntary disclosure enables all the concerned parties obtaining more relevantinformation about the strategies and critical elements of the fi rms. In this study, we examinedthe impact of corporate governance and fi nancial distress condition on the level of voluntary informationdisclosure. This research used a sample of manufacture fi rms listed in Indonesian stockexchange. Based on data processing using sample above, we found that corporate governance andfi nancial distress could be associated with the voluntary disclosure level.